Metropolitan police service user satisfaction survey, 2005/06-2017/18 (UK Data Service, 2019)
The Metropolitan Police Service User Satisfaction Survey (MPS USS) (formerly known as the Crime Victim Survey) is a corporate survey tool used to measure crime victims' satisfaction with a specific instance of their contact with police. The survey covers the process from initial contact with police, through to police action and follow-up, whilst considering police treatment throughout the process. These elements feed into the main measure of 'Overall Satisfaction', and the results feed into the 'Citizen Focus' domain of Home Office measures. The Overall Satisfaction measure is further explored in order to monitor difference in satisfaction between white and black and minority ethnic (BME) groups, as well as victims of racist incidents. The results are gathered through telephone interviews with c. 18,000 victims a year, by an external market research company on behalf of the MPS. Victims are interviewed 6-12 weeks after they have reported the crime, and interviewing takes place throughout the year. The file currently includes data from 32 quarters between 2005/6 and 2017/18, though the documentation largely covers 2011 onwards. The sample includes victims of burglary, violent crime, vehicle crime, racially-motivated and homophobic crime, between the ages of 16 to 85 years. It excludes victims of domestic violence, serious assaults and sexual offences. Road Traffic Collision victims have not been surveyed since the fiscal year 2012-13. The USS data is reported quarterly within the MPS, and is also provided to the Home Office and Her Majesty's Inspectorate of Constabulary (HMIC).